High temperature resistant coated sand for casting and preparation method thereof

By adding modified phenolic resin, paraformaldehyde, silicone polymer and other ingredients to the coated sand, a high-temperature-resistant coated sand is prepared, which solves the problem that the existing coated sand is prone to sand core cracking and sand sticking during the high-temperature casting process, and significantly improves heat resistance and compressive strength.

CN115229122BActive Publication Date: 2025-04-18LIUZHOU LIUJING ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210790852.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-05
Publication Date
2025-04-18
Estimated Expiration
2042-07-05

AI Technical Summary

Technical Problem

During the high-temperature casting process, existing coated sand is prone to sand cracking and sand sticking on the surface of castings, mainly due to its insufficient high-temperature resistance and cannot withstand the high-temperature impact of molten iron.

Method used

A high-temperature-resistant coated sand is prepared by adding modified phenolic resin, paraformaldehyde, silicone polymer, ethylene glycol and polyphenylene ether to the coated sand. The curing temperature of the modified phenolic resin is reduced and the viscosity is reduced. Paraformaldehyde and silicone polymers improve the heat resistance and compressive strength of the coated sand.

Benefits of technology

It significantly improves the heat resistance and compressive strength of coated sand, solves the problems of sand core cracking and sand sticking, and broadens the application range of coated sand in different climatic conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high temperature resistant coated sand for casting and a preparation method thereof; the phenolic resin is modified by adding an organosilicon polymer, ethylene glycol, boric acid, resorcinol and polyphenylene ether into the phenolic resin. By utilizing the mutual synergistic effect between the substances, a coated sand with high fluidity, high strength, low curing temperature and high heat resistance is prepared. Resorcinol and polyphenylene ether reduce the curing temperature of the modified phenolic resin; ethylene glycol greatly reduces the viscosity of the modified phenolic resin by increasing the molecular weight of the modified phenolic resin; the high temperature curing of the organosilicon polymer itself enhances the heat resistance of the coated sand; the inorganic structure formed by cross-linking between the organosilicon polymer, ethylene glycol and boric acid enhances the compressive strength of the coated sand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coated sand, in particular to high temperature resistant coated sand for casting and a preparation method thereof. Background Art

[0002] With the rapid development of the foundry industry, people are no longer satisfied with the performance of coated sand with high tensile strength and low gas emission. In the actual production process, ordinary coated sand is prone to cracking of sand core and sand sticking on the surface of castings during high-temperature pouring of steel castings. The reason is that the high-temperature resistance of coated sand is not enough and it cannot withstand the high-temperature impact of molten iron, which causes molten iron to penetrate into the coated sand during the casting process, resulting in a series of problems such as cracking.

[0003] Therefore, it is of great significance to prepare a high temperature resistant coated sand for casting. Summary of the invention

[0004] The object of the present invention is to provide a high temperature resistant coated sand for casting and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing high temperature resistant coated sand for casting comprises the following steps:

[0007] S1: preheat the raw sand and add it into the sand mixer to mix the sand;

[0008] S2: Mix the modified phenolic resin and polyformaldehyde and add them into a sand mixer, stir and mix the sand to obtain high temperature resistant coated sand for casting.

[0009] Furthermore, in step S2, the amount of modified phenolic resin added is 2-3% of the mass of the original sand, and the mass ratio of modified phenolic resin to paraformaldehyde is 1:1.

[0010] Furthermore, in step S2, the modified phenolic resin is prepared as follows:

[0011] The phenol is melted and added into a reaction container, stirred, formaldehyde, potassium hydroxide and sodium hydroxide are added, stirred and heated to react, resorcinol is added, stirred at a constant temperature, boric acid is added, refluxed, and distilled under reduced pressure. After cooling, an organosilicon polymer and a silane coupling agent are added, stirred, a modifier is added, stirred, and a modified phenolic resin is obtained.

[0012] Furthermore, the mass ratio of formaldehyde, phenol, potassium hydroxide, sodium hydroxide and resorcinol is 10:5:5:1:(2.5-3), the stirring and heating reaction temperature is 70-75° C., and the stirring and heating reaction time is 1.5-2 h.

[0013] Furthermore, the amount of the organic silicon polymer added is 5-25% of the total mass of phenol, formaldehyde, potassium hydroxide and sodium hydroxide, and the mass ratio of the silane coupling agent to the organic silicon polymer is (0.2-0.5): 1. Furthermore, the mass ratio of the boric acid to the organic silicon polymer is 1:1; the reflux time is 40-60 minutes, and the reduced pressure distillation time is 1-2 hours.

[0014] Furthermore, the modifier is ethylene glycol and polyphenylene ether, the amount of the modifier added is 20-30% of the total mass of phenol, formaldehyde, potassium hydroxide and sodium hydroxide, and the mass ratio of ethylene glycol to polyphenylene ether in the modifier is 1:2.

[0015] Furthermore, the organosilicon polymer is prepared as follows:

[0016] (1) under a nitrogen atmosphere, tetrahydrofuran, anhydrous ether and n-butyl lithium are added to a reaction container and stirred at low temperature; an anhydrous ether solution of trichloroethylene is added to the reaction container and reacted at low temperature; a tetrahydrofuran solution of diphenyldichlorosilane is added to the reaction container and reacted at low temperature; suction filtration, washing, and reduced pressure distillation are performed to obtain polydiphenylethynylsilane;

[0017] (2) adding polydiphenylethynylsilane and anhydrous ethanol to a reaction vessel and stirring at low temperature; adding an anhydrous ether solution of trifluoromethanesulfonic acid to a reaction vessel and stirring at low temperature; and performing reduced pressure distillation to obtain a polytrifluoromethanesulfonic acid phenylethynylsilane intermediate;

[0018] (3) adding lithium aluminum hydride and anhydrous ether into a reaction vessel and stirring at low temperature; adding an anhydrous ether solution of the polytrifluoromethanesulfonylphenylethynylsilane intermediate into the reaction vessel at low temperature, heating to room temperature and stirring for reaction; washing with saturated sodium chloride, filtering, drying with anhydrous magnesium sulfate, and distilling under reduced pressure to obtain an organosilicon polymer.

[0019] Furthermore, in step (1), the low-temperature stirring temperature is -30°C and the stirring time is 2 hours; the reduced pressure distillation temperature is 60-70°C; the low-temperature reaction temperature in step (2) is -20°C and the reaction time is 3-3.5 hours; in step (3), the room temperature stirring reaction time is 12-14 hours.

[0020] Another aspect of the present invention provides coated sand prepared by the above method.

[0021] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: by adding resorcinol and polyphenylene ether, the unreacted methylol in the system continues to condense, and the ether bond is converted into methylene, which greatly reduces the curing temperature of the modified phenolic resin, ensures that the coated sand can be used for production applications under cold climate conditions in actual production, and broadens the application range of the coated sand.

[0022] The invention increases the molecular weight of the modified phenolic resin by adding ethylene glycol, thereby greatly reducing the viscosity of the modified phenolic resin, and solving the problems of high viscosity, poor fluidity, difficulty in filling and uneven mixing of the traditional phenolic resin.

[0023] The present invention enhances the heat resistance of the modified phenolic resin by adding an organosilicon polymer. The organosilicon polymer itself forms an organic structure solidified product containing olefins, benzene rings and condensed rings at high temperatures, reducing the overflow of volatile oligomers; when the temperature continues to rise, the organic structure in the solidified product begins to transform into an inorganic structure, forming a ceramic phase with better high-temperature stability, thereby enhancing the heat resistance of the coated sand. The organosilicon polymer also contains a large number of silicon-hydrogen bonds that react with the silane coupling agent KH550 to provide a large number of -SiOH, and boric acid provides a large number of borate radicals. When the modified phenolic resin is at high temperature, the carboxyl and hydroxyl groups generated by the oxidation of the end groups undergo molecular chain crosslinking as the temperature rises, generating a large number of boron-oxygen bonds and silicon-oxygen bond inorganic structures, thereby further enhancing the heat resistance of the coated sand.

[0024] While ethylene glycol reduces the viscosity of modified phenolic resin, the active hydroxyl groups it contains will undergo a cross-linking reaction with the resin and the silicone polymer, thereby enhancing the compressive strength of the coated sand. At the same time, ethylene glycol can also undergo a coordination reaction with boric acid, further enhancing the compressive strength of the coated sand. The curing of the silicone polymer at high temperature and the inorganic structure generated by the cross-linking reaction of the hydroxyl and carboxyl groups of the modified phenolic resin further enhance the compressive strength of the coated sand.

[0025] The invention prepares coated sand with high strength, low curing temperature and high heat resistance through the synergistic effect of organic silicon polymer, ethylene glycol, boric acid, resorcinol and polyphenylene ether in modified phenolic resin. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the following examples, the organosilicon polymers were prepared as follows:

[0028] Under a nitrogen atmosphere, 10 mL of tetrahydrofuran, 10 mL of anhydrous ether and 40 mmol of n-butyl lithium were added to a reaction container, and stirred at -30°C for 2 h; 13.5 mmol of trichloroethylene and 10 mL of anhydrous ether were mixed, and then added to a reaction container, and reacted at -30°C for 2 h; 10 mL of tetrahydrofuran and 13.5 mmol of diphenyldichlorosilane were mixed, and then added to a reaction container, and reacted at -30°C for 2 h; filtered, washed until neutral, and distilled under reduced pressure at 60°C until the solvent evaporated to obtain polydiphenylethynylsilane;

[0029] 3 g of polydiphenylethynylsilane and 10 mL of anhydrous ethanol were added to a reaction container, and stirred at -30°C for 2 h; 13.5 mmol of trifluoromethanesulfonic acid and 50 mL of anhydrous ether were mixed, and then quickly dripped into the reaction container, and stirred at -20°C for 3 h; and distilled under reduced pressure at 60°C until the solvent evaporated to obtain a polytrifluoromethanesulfonic acid phenylethynylsilane intermediate;

[0030] 6.5 mmol lithium aluminum hydride and 60 mL anhydrous ether were added to a reaction vessel, and stirred at -30°C for 2 h. The polytrifluoromethanesulfonylphenylethynylsilane intermediate and 30 mL anhydrous ether were mixed, and added to the reaction vessel at low temperature. After the addition was completed, the mixture was heated to room temperature and stirred for 12 h. The mixture was washed with saturated sodium chloride, filtered, dried with anhydrous magnesium sulfate, and the solvent was distilled off under reduced pressure to obtain an organosilicon polymer.

[0031] In the following examples, the silane coupling agent is KH550.

[0032] Example 1

[0033] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0034] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 2.5 g of resorcinol was added, stirred at 70°C for 2 h, 1.05 g of boric acid was added, refluxed for 60 min, and distilled under reduced pressure for 2 h. After cooling, 1.05 g of organosilicon polymer and 0.21 g of silane coupling agent KH550 were added, stirred, 1.4 g of ethylene glycol and 2.8 g of polyphenylene ether were added, stirred to obtain a modified phenolic resin;

[0035] S3: 20 g of modified phenolic resin and 20 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0036] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample. 2CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0037] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0038] Example 2

[0039] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0040] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 2.7 g of resorcinol was added, stirred at 70°C for 2 h, 1.05 g of boric acid was added, refluxed for 60 min, and distilled under reduced pressure for 2 h. After cooling, 1.05 g of organosilicon polymer and 0.42 g of silane coupling agent KH550 were added, stirred, 1.4 g of ethylene glycol and 2.8 g of polyphenylene ether were added, stirred to obtain a modified phenolic resin;

[0041] S3: 20 g of modified phenolic resin and 20 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0042] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample. 2 CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0043] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0044] Example 3

[0045] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0046] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 3 g of resorcinol was added, stirred at 70°C for 2 h, 1.05 g of boric acid was added, refluxed for 60 min, and distilled under reduced pressure for 2 h. After cooling, 1.05 g of organosilicon polymer and 0.525 g of silane coupling agent KH550 were added, stirred, 1.4 g of ethylene glycol and 2.8 g of polyphenylene ether were added, stirred to obtain a modified phenolic resin;

[0047] S3: 20 g of modified phenolic resin and 20 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0048] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample.2 CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0049] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0050] Example 4

[0051] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0052] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 2.5 g of resorcinol was added, stirred at 70°C for 2 h, 3.15 g of boric acid was added, refluxed for 60 min, and distilled under reduced pressure for 2 h. After cooling, 3.15 g of organosilicon polymer and 1.575 g of silane coupling agent KH550 were added, stirred, 1.4 g of ethylene glycol and 2.8 g of polyphenylene ether were added, stirred to obtain a modified phenolic resin;

[0053] S3: 20 g of modified phenolic resin and 20 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0054] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample. 2 CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0055] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0056] Example 5

[0057] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0058] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 3 g of resorcinol was added, stirred at 70°C for 2 h, 5.25 g of boric acid was added, refluxed for 60 min, and distilled under reduced pressure for 2 h. After cooling, 5.25 g of organosilicon polymer and 2.625 g of silane coupling agent KH550 were added, stirred, 1.4 g of ethylene glycol and 2.8 g of polyphenylene ether were added, stirred to obtain a modified phenolic resin;

[0059] S3: 20 g of modified phenolic resin and 20 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0060] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample. 2 CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0061] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0062] Example 6

[0063] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0064] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 2.5 g of resorcinol was added, stirred at 70°C for 2 h, 5.25 g of boric acid was added, refluxed for 60 min, and distilled under reduced pressure for 2 h. After cooling, 5.25 g of organosilicon polymer and 2.625 g of silane coupling agent KH550 were added, stirred, 2.1 g of ethylene glycol and 4.2 g of polyphenylene ether were added, stirred, and a modified phenolic resin was obtained;

[0065] S3: 30 g of modified phenolic resin and 30 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0066] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample. 2 CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0067] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0068] Comparative Example 1 (the organosilicon modifier is phenyltrimethoxysilane)

[0069] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0070] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 2.5 g of resorcinol was added, stirred at 70°C for 2 h, 1.05 g of boric acid was added, refluxed for 60 min, and vacuum distilled for 2 h. After cooling, 1.05 g of phenyltrimethoxysilane and 0.21 g of silane coupling agent KH550 were added, stirred, 1.4 g of ethylene glycol and 2.8 g of polyphenylene ether were added, stirred to obtain a modified phenolic resin;

[0071] S3: 20 g of modified phenolic resin and 20 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0072] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample. 2 CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0073] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0074] Comparative Example 2 (without adding resorcinol)

[0075] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0076] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 1.05 g of boric acid was added, refluxed for 60 min, and vacuum distilled for 2 h. After cooling, 1.05 g of organosilicon polymer and 0.21 g of silane coupling agent KH550 were added, stirred, 1.4 g of ethylene glycol and 2.8 g of polyphenylene ether were added, and the modified phenolic resin was obtained;

[0077] S3: 20 g of modified phenolic resin and 20 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0078] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample. 2 CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0079] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0080] Comparative Example 3 (Modifiers are triethylene glycol and polyphenylene ether)

[0081] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0082] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 2.5 g of resorcinol was added, stirred at 70°C for 2 h, 1.05 g of boric acid was added, refluxed for 60 min, and distilled under reduced pressure for 2 h. After cooling, 1.05 g of organosilicon polymer and 0.21 g of silane coupling agent KH550 were added, stirred, 1.4 g of triethylene glycol and 2.8 g of polyphenylene ether were added, stirred to obtain a modified phenolic resin;

[0083] S3: 20 g of modified phenolic resin and 20 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0084] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample. 2 CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0085] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0086] Comparative Example 4 (Silane coupling agent is KH570)

[0087] S1: preheat 1000g of raw sand and add it into the sand mixer to mix the sand;

[0088] S2: 5 g of phenol was melted and added to a reaction container, stirred, 10 g of formaldehyde, 5 g of potassium hydroxide and 1 g of sodium hydroxide were added, the temperature was raised to 70°C, stirred and reacted for 2 h, 2.5 g of resorcinol was added, stirred at 70°C for 2 h, 1.05 g of boric acid was added, refluxed for 60 min, and distilled under reduced pressure for 2 h. After cooling, 1.05 g of organosilicon polymer and 0.21 g of silane coupling agent KH570 were added, stirred, 1.4 g of ethylene glycol and 2.8 g of polyphenylene ether were added, stirred to obtain a modified phenolic resin;

[0089] S3: 20 g of modified phenolic resin and 20 g of polyformaldehyde are mixed and added into a sand mixer to mix the sand to obtain high temperature resistant coated sand for casting.

[0090] Test: The coated sand was impacted three times on a SAC hammer-type sample making machine to make a 50mm×50mm×50mm sample. 2 CO2 was blown in at a flow rate of 1000 nm to harden the sand and obtain a coated sand sample.

[0091] Thermogravimetric analysis and compressive strength tests were performed, see the table below.

[0092] Coated sand sample test

[0093] Initial decomposition temperature / ℃ Compressive strength / MPa Example 1 470 2.8 Example 2 492 2.9 Example 3 512 2.9 Example 4 523 3.2 Example 5 535 3.5 Example 6 545 3.7 Comparative Example 1 432 2.5 Comparative Example 2 411 2.4 Comparative Example 3 398 2.2 Comparative Example 4 452 2.6

[0094] Conclusion: Examples 1 to 6 show that when the mass ratio of formaldehyde, phenol, potassium hydroxide, sodium hydroxide and resorcinol is 10:5:5:1:2.5, the amount of silicone polymer added is 25% of the total mass of phenol, formaldehyde, potassium hydroxide and sodium hydroxide, and the amount of modifier added is 20-30% of the total mass of phenol, formaldehyde, potassium hydroxide and sodium hydroxide, the prepared coated sand has the best heat resistance and compressive strength.

[0095] In Comparative Example 1, the silicone modifier phenyltrimethoxysilane was used to replace the silicone polymer, resulting in a decrease in the heat resistance and compressive strength of the prepared coated sand. Phenyltrimethoxysilane itself cannot be cured to form an organic structure solid containing olefins, benzene rings and condensed rings, nor can it be transformed into an inorganic structure to form a ceramic phase with better high-temperature stability.

[0096] In Comparative Example 2, no meta-diphenol was added to the modified phenolic resin, resulting in a decrease in the heat resistance and compressive strength of the coated sand. The addition of meta-diphenol can reduce the curing temperature of the coated sand and enable the phenolic resin to undergo a better condensation reaction, thereby reducing the number of unreacted groups during the curing process of the coated sand.

[0097] In Comparative Example 3, triethylene glycol was used instead of ethylene glycol, resulting in the coated sand having too low viscosity, and the heat resistance and compressive strength were reduced.

[0098] In Comparative Example 4, KH570 was used instead of KH550, resulting in reduced heat resistance of coated sand. This is because KH570 does not contain amine catalyst and cannot be dehydrogenated to generate -SiOH, thus generating an inorganic structure of silicon-oxygen bonds.

[0099] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing high temperature resistant coated sand for casting, characterized in that: The following steps are involved: S1: preheat the raw sand and add it into the sand mixer to mix the sand; S2: Mixing the modified phenolic resin and the polyformaldehyde and adding them into a sand mixer, stirring and mixing the sand to obtain high temperature resistant coated sand for casting; In step S2, the modified phenolic resin is prepared as follows: The phenol is melted and added to a reaction container, stirred, formaldehyde, potassium hydroxide and sodium hydroxide are added, stirred and heated to react, resorcinol is added, stirred at a constant temperature, boric acid is added, refluxed, and distilled under reduced pressure, and after cooling, an organosilicon polymer and a silane coupling agent are added, stirred, a modifier is added, stirred, and a modified phenolic resin is obtained; The silicone polymer was prepared as follows: (1) under a nitrogen atmosphere, tetrahydrofuran, anhydrous ether and n-butyl lithium are added to a reaction container and stirred at low temperature; an anhydrous ether solution of trichloroethylene is added to the reaction container and reacted at low temperature; a tetrahydrofuran solution of diphenyldichlorosilane is added to the reaction container and reacted at low temperature; suction filtration, washing, and reduced pressure distillation are performed to obtain polydiphenylethynylsilane; (2) adding polydiphenylethynylsilane and anhydrous ethanol to a reaction vessel and stirring at low temperature; adding an anhydrous ether solution of trifluoromethanesulfonic acid to a reaction vessel and stirring at low temperature; and performing reduced pressure distillation to obtain a polytrifluoromethanesulfonic acid phenylethynylsilane intermediate; (3) adding lithium aluminum hydride and anhydrous ether into a reaction vessel and stirring at low temperature; adding an anhydrous ether solution of the polytrifluoromethanesulfonylphenylethynylsilane intermediate into the reaction vessel at low temperature, heating to room temperature and stirring for reaction; washing with saturated sodium chloride, filtering, drying with anhydrous magnesium sulfate, and distilling under reduced pressure to obtain an organosilicon polymer.

2. The method for preparing high temperature resistant coated sand for casting according to claim 1, characterized in that: In step S2, the amount of modified phenolic resin added is 2-3% of the mass of the original sand, and the mass ratio of modified phenolic resin to paraformaldehyde is 1:

1.

3. The method for preparing high temperature resistant coated sand for casting according to claim 1, characterized in that: The mass ratio of formaldehyde, phenol, potassium hydroxide, sodium hydroxide and resorcinol is 10:5:5:1:(2.5-3), the stirring and heating reaction temperature is 70-75°C, and the stirring and heating reaction time is 1.5-2h.

4. The method for preparing high temperature resistant coated sand for casting according to claim 1, characterized in that: The amount of the organic silicon polymer added is 5-25% of the total mass of phenol, formaldehyde, potassium hydroxide and sodium hydroxide, and the mass ratio of the silane coupling agent to the organic silicon polymer is (0.2-0.5):

1.

5. The method for preparing high temperature resistant coated sand for casting according to claim 1, characterized in that: The mass ratio of boric acid to silicone polymer is 1:1; the reflux time is 40 to 60 minutes, and the reduced pressure distillation time is 1 to 2 hours.

6. The method for preparing high temperature resistant coated sand for casting according to claim 1, characterized in that: The modifiers are ethylene glycol and polyphenylene ether, the amount of the modifier added is 20-30% of the total mass of phenol, formaldehyde, potassium hydroxide and sodium hydroxide, and the mass ratio of ethylene glycol to polyphenylene ether in the modifier is 1:

2.

7. The method for preparing high temperature resistant coated sand for casting according to claim 1, characterized in that: In step (1), the low-temperature stirring temperature is -30°C and the stirring time is 2 hours; the reduced pressure distillation temperature is 60-70°C; in step (2), the low-temperature reaction temperature is -20°C and the reaction time is 3-3.5 hours; in step (3), the room temperature stirring reaction time is 12-14 hours.

8. The coated sand obtained according to the method for preparing high temperature resistant coated sand for casting according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Coated sand recycling method

    CN106607546A

  • Method for preparing regenerated precoated sand from waste precoated sand

    CN115041628A